Market Value and Sporting Performance of Football Clubs - Luciano Bernardes Leite; Leôncio Lopes Soares; Leonardo Mateus Teixeira de Rezende; Guilherme de Azambuja Pussieldi (Universidade Salgado de Oliveira, 2020)
The objective of this work was to evaluate the relationship between market value and sports performance of soccer clubs in different world championships (Spanish, English, Brazilian, Italian, French). The sample consisted of football clubs (n = 100) that competed in the national championship in the first division of their respective countries in the last five seasons (2013-2014 to 2017-2018, European calendar) and (2014 to 2018, Brazilian calendar). The variables final score and market value of the clubs in the season were correlated by Spearman's correlation test, adopting p <0.05 as significant values. The results showed weak to strong correlations between the clubs' market values and sports performance in all championships in the last five seasons. When analyzing the data separately, it is observed that the Italian championship presented the highest correlation (0.91) in the 2017/2018 season. On the other hand, the lowest correlation observed was in the English league (0.41) in the 2015/2016 season. The results of the present study showed a relationship between market values and the final classification of football clubs, that is, clubs that invest the most are likely to become champions.